Institutional Embeddedness and Financial Socialization: The Sociological Impact of the Campus Investment Gallery on Student Stock Investment Interest in a 3-in-1 Capital Market Partnership - Juliet Pauladel Truly Makinggung; Jemmry Recy Winokan; Kevin Pangemanan; Heidy Pesik (Baileo: Jurnal Sosial Humaniora, 2026)
This study aims to analyze how the Campus Investment Gallery (CIG), operating within a 3-in-1 partnership between higher education institutions, the Indonesia Stock Exchange, and securities companies, becomes an institutionally embedded mechanism that shapes students’ financial socialization and their interest in stock investment. Addressing the persistent issue of low capital market literacy among students, the research employs a descriptive quantitative approach enriched by economic sociology interpretation. Conducted at Manado State Polytechnic with 80 Business Administration students, data were collected through observations, short interviews, Likert-scale questionnaires, and literature review. Simple linear regression, t-tests, correlation coefficients, and the coefficient of determination were processed using SPSS 26 and interpreted through embeddedness theory and financial socialization concepts. The findings demonstrate a positive and significant influence of the CIG on students’ investment interest, reflected in a high t-value (9.694 > 2.037), strong correlations (r = 0.687–0.817), and determination values ranging from 47.2% to 64%. The CIG acts as a financial socialization agent through knowledge transfer, engagement with practitioners, and direct exposure to investment instruments, while the 3-in-1 partnership provides legitimacy and an institutional network that fosters new economic habitus among students. The study offers novelty by integrating economic sociology into capital market education and conceptualizing the CIG as a hybrid institution shaping youth economic behavior, contributing to broader theoretical development on embeddedness and financial socialization.